Project-Based Learning: Analysis of the Otto Robot Commercialization in Terms of Business Aspect, Costing, and Operating Budget - Rossa Sharonica; Sugeng Riadi (Pusat P2M Politeknik Negeri Batam, 2023)
This research discusses the commercialization analysis of the Otto Robot in terms of business, costing, and operating budget aspects. The purpose of this research is to find out the cost of sales of Robot Otto and to make Standard Cost Sheets and Operating Budgets as a basis for evaluating performance at Barelang Roboschool BRAIL Batam State Polytechnic. This research used a qualitative method with a project-based learning approach based on primary and secondary data. Data collection was carried out using documentation techniques, interviews, and direct observation at the research site. The results of indicating that the calculation of the Operating Budget can be used as a tool to analyze the operational income and expenses of Roboschool BRAIL Batam State Polytechnic in a 5-month period, the creation of a Standard Costing Sheet as a determinant of the cost of the product Otto Robot produced as well as the results of Porter's Five Forces analysis and SWOT analysis are used to know the business conditions and be able to implement strategies that suit the conditions.